Transformation of symbolism in healthy food advertising: Charles Sanders Peirce's semiotic analysis of healthy lifestyle trends on social media - Arya Megananda; M. Fikri Akbar; Sandy Allifiansyah (Journal of Education, Social & Communication Studies, 2026)
Changes in healthy lifestyle trends in the digital era have triggered an increase in healthy food advertisements circulating on various social media platforms. These advertisements not only function as a means of product promotion but also as a medium for constructing new symbols related to the concept of health. This study aims to analyse the transformation of symbolism in healthy food advertisements using Charles Sanders Peirce's semiotic approach, which emphasizes the triadic relationship between representamen, object, and interpretant, as well as the classification of signs into icons, indices, and symbols. The research method used is qualitative with semiotic analysis techniques on a number of healthy food advertisements uploaded on Instagram and TikTok from January to June 2025. The results show a dominant shift from the use of visual icons, such as images of fresh food, to activity indices that associate products with an active lifestyle, as well as symbols that position health as a social identity and prestigious aspiration. This transformation illustrates how healthy food is positioned not only as a nutritional need, but also as a representation of a modern lifestyle and certain moral values. Further discussion links these findings with previous literature and highlights the ethical implications of advertising strategies that focus on identity symbolism. The study's conclusions emphasize that healthy food advertising on social media plays a significant role in shaping public perceptions of the meaning of "healthy," which is no longer solely biological but also cultural and symbolic.